High Attachment in Thai Learners’ Processing of English Relative Clauses - Wang, Jie; Singhapreecha, Pornsiri (LEARN Journal: Language Education and Acquisition Research Network, 2022)
Resolution to ambiguity imposed by English relative clauses (RC) was examined with Thai EFL students in this study. Offline experimental items included two-site context NPs, i.e., NP1 of NP2 (Complex NP of) and NP1 with NP2 (Complex NP with) modified by RCs. As NP1 and NP2 occupy higher and lower positions in the hierarchical structure of a complex NP, RC attachment to NP1 and NP2 are termed High Attachment (HA) and Low Attachment (LA). It was hypothesized that the RC would be attached to NP1 in the Complex NP of, and NP2 in the Complex NP with, based on the Thai L1 strategy and the universal properties of thematic prepositions, respectively. Three proficiency levels, i.e., beginning, intermediate, and upper-intermediate, were established for the participants. The results confirmed both predictions. In addition, there were a rise and decline across the three proficiency levels in the employment of HA for the Complex NP of and a continuous and significant increase in the employment of LA for the Complex NP with. Overall, this study suggests the influence of an L1 strategy and the development of an L2 strategy in the absence of a corresponding L2 structure, in association with L2 employment of thematic information.